Diskresi dalam Implementasi Kebijakan Publik (Studi pada Implementasi Kebijakan BPJS-Kesehatan di Puskesmas Kepanjen) - Pradana, Gatu Adie (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
BPJS-Kesehatan Policy as a top-down policy, Puskesmas position as the spearhead of health services, especially in Puskesmas Kepanjen Malang District. Issues that exist in this research is how the pattern of discretion occurs and how its impact on BPJS-Kesehatan policy implementation in the Puskesmas Kepanjen. Discretion occur at managerial levels, the changing patterns of communication and coordination by the Office of BPJS-Kesehatan, Public Health Service of Malang Regency and Puskesmas Kepanjen. There are several steps that can be taken to overcome such discretion. First the capitation system changes; strengthening and centralizing the BPJS-Kesehatan database; and the regulations that health centers can manage a budget independently.